Typology of Words and Constructions with a High Degree of Meaning - E. R. Ioanesyan (Научный диалог, 2021)
The article is devoted to the study of the semantics of units expressing the value of intensity. The concept of the lexical function Magn of the “Meaning ↔ Text” model is used in the article. Lexical functions are a tool for describing limited lexical collocation. Magn is an abstract typical meaning of ‘very’, ‘intensity’, ‘high degree’, which is expressed in a significant number of different words, and in many cases in an idiomatic way.  Lexical units expressing the meaning of ‘very’ / ‘large’ / ‘intense’ are represented in different languages by a large number of words and constructions. The designation of intensity in many languages has lexically determined variants of expression, often linguistic specific. A brief overview of the main models of the formation of the meaning of intensity in a language, examples of linguistic-specific units are given. The novelty of the research is determined by the presentation in the work of new models of the formation of the meaning of Magn and linguistic-specific expressions of this meaning. The relevance of the study is due to the fact that the study of models of the formation of the value of intensity is in line with modern research on the study of semantic evolution, the construction of a typology of semantic transitions, the identification of the features of the picture of the world of different languages, the creation of explanatory models of the language.